A modification of the Abbe Estlander flap for lip defect reconstruction near the angle of the mouth - Ghodasara, Sonali D.; Sakariya, Grishma M.; Rojesara, Meet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Lips play an essential role in aesthetics and in vital functions such as nutrition and speech. The complex anatomy of the lips-comprising three distinct layers of skin, muscle, and mucosa-makes surgical management of this region a therapeutic challenge. Excision of malignant tumors is the most frequent cause of tissue loss. The abundant blood supply of the lips allows the use of flaps for reconstruction of large defects with minimal risk of necrosis. Squamous cell carcinoma is the most common malignancy affecting the lips, and the lower lip is most frequently involved. This study was conducted at the Department of Surgical Oncology, Saurashtra Cancer Care Research and Institute, Rajkot.